Intersemiosis Elemen Verbal-Visual dalam Penyampaian Makna pada Website Fundraising di Korea Selatan - Inggri Dwi Ramjani; Velayeti Nurfitriana Ansas; Arif Husein Lubis (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
Nonprofit fundraising websites now function as multimodal communication spaces that integrate verbal and visual elements into a single system of meaning. This study analyzes the construction of ideational meaning on three South Korean NGO fundraising websites (Good Neighbors Korea, Community Chest of Korea, Green Umbrella ChildFund Korea) featuring campaigns to assist vulnerable children. The study employs a Multimodal Discourse Analysis approach using three frameworks: the transitivity framework of Systemic Functional Linguistics for verbal elements (Kim et al., 2023), representational meaning and types of narrative processes for visual elements (Kress & van Leeuwen, 2006), and Unsworth’s (2006) concept of intersemiosis for intermodal relationships. Data were collected in November 2025 through digital documentation of 29 screenshots, yielding 224 verbal clauses. The results show that verbal representations were dominated by P2: Undergoer and material processes, while visual representations were dominated by conceptual symbolic representations—particularly food objects interpreted as symbols of need. Intersemiosis relationships were equally dominated by Concurrence: exposition and complementarity: augmentation (text extends image), indicating that the text expands the visual meaning by adding social context and the rationale for the need for assistance. These findings confirm that fundraising websites are multimodal spaces where language and visuals work together to construct social meaning about vulnerable children, with implications for the design of nonprofit digital fundraising messages so that social issues are understood more concretely and contextually.